2002
DOI: 10.1055/s-2002-36699
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Plasminogen Activator Inhibitor-1 with Fibrin Deposition in a Murine Model of Aging, "Klotho" Mouse

Abstract: Although aging accompanies specific pathological changes, including thrombosis and organ sclerosis, the underlying mechanisms of these processes remain to be elucidated. In the present study, we analyzed the gene expression of plasminogen activator inhibitor-1 (PAI-1), a key molecule in the development of thrombosis, in a murine model of aging, klotho mutant ( kl/kl) mice. Active PAI-1 antigen in plasma and PAI-1 mRNA in several tissues were strikingly elevated in kl/kl mice as compared with wild-type mice. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 24 publications
(31 reference statements)
3
49
0
2
Order By: Relevance
“…Nitric oxide interferes with vascular calcification by regulating Pai1 (42). Enhanced Pai1 expression has similarly been observed in the kl/kl mice (43). However, the phenotype of the kl/kl mice and the FGF23 knockout mice results from excessive formation of 1,25(OH) 2 D 3 and subsequent hyperphosphatemia, as it is reversed by vitamin Ddeficient or low phosphate diet (27,(44)(45)(46) 2+ and phosphate concentrations, it suppresses NF-κB and TNF-α (49), which in turn are involved in the stimulation of vascular calcification (50)(51)(52).…”
Section: Figurementioning
confidence: 86%
“…Nitric oxide interferes with vascular calcification by regulating Pai1 (42). Enhanced Pai1 expression has similarly been observed in the kl/kl mice (43). However, the phenotype of the kl/kl mice and the FGF23 knockout mice results from excessive formation of 1,25(OH) 2 D 3 and subsequent hyperphosphatemia, as it is reversed by vitamin Ddeficient or low phosphate diet (27,(44)(45)(46) 2+ and phosphate concentrations, it suppresses NF-κB and TNF-α (49), which in turn are involved in the stimulation of vascular calcification (50)(51)(52).…”
Section: Figurementioning
confidence: 86%
“…kl/kl mice exhibit a remarkable increase in plasma levels of FGF23, as well as significant increases in serum levels of calcium, phosphate, vitamin D 3 , and creatinine (13). Interestingly, kl/kl mice also have an age-dependent increase in plasma PAI-1 levels as well as increased PAI-1 expression in a number of tissues including kidney, aorta, and heart (18). Because PAI-1 is necessary and sufficient to induce replicative senescence in vitro downstream of p53 (19) and is markedly increased in kl/kl mice, we hypothesized that PAI-1 is a critical determinant of the phenotypic abnormalities developed by kl/kl mice.…”
Section: Fgf23 | Igfbp3 | Il-6 | Tm5441mentioning
confidence: 99%
“…Takeshita et al noted age-dependent increases in Pai1 expression and fibrin deposition in the Klotho mouse, a murine model of aging. 76 Yamamoto et al found pronounced increases in tissue factor and Pai1 gene expression in aged mice subjected to restraint stress. 77,78 By quantitating fibrin deposition and intravascular thrombosis, we have found that the factor V Leiden mouse has also been useful to elucidate prothrombotic phenotypes in mice that develop age-related vascular disease.…”
Section: Westrick Et Al Murine Models Of Vascular Thrombosis 2087mentioning
confidence: 99%